HEMOSTATIC DISORDERS IN LIVER DISEASES - A. F. Minov; A. M. Dzyadzko; O. O. Rummo (Вестник трансплантологии и искусственных органов)
The liver is an essential player in the pathway of coagulation in both primary and secondary hemostasis as it is the site of synthesis of all coagulation factors and their inhibitors. Liver diseases are associated with complex changes in coagulation and the delicate balance between pro and antithrombotic factors is preserved but reset to a lower level. There is growing evidence that portal and hepatic vein thrombosis is cause of disease progression in cirrhotic patients and worsens hemostatic abnormalities. These hemostatic abnormalities do not always lead to spontaneous bleeding, which may be triggered only by additional factors, such as infections. Usually therapy for coagulation disorders in liver disease is needed only during bleeding or before invasive procedures. In patients with end stage liver disease liver transplantation is the only treatment available, which can restore normal hemostasis, and correct genetic clotting defects. During liver transplantation hemorrhage may occur due to the pre-existing hypocoagulable state, the collateral circulation caused by portal hypertension and increased fibrinolysis.